2005
DOI: 10.1080/09585170500384586
|View full text |Cite
|
Sign up to set email alerts
|

Formative assessment for all: a whole‐school approach to pedagogic change

Abstract: AcknowledgementsThe authors gratefully acknowledge the advice given by Nick Boreham and Richard Edwards during the drafting of this paper. We are, of course, indebted to the staff at Discovery School for their willing participation in the research project.Formative assessment for all: a whole school approach to pedagogic change Scotland's Assessment is for Learning initiative (AifL) seeks to introduce a coordinated national system for assessment in schools. Formative assessment is a major plank in this. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In later interviews, many had either gained confidence to pursue their individual developmental goals or recognised that the concerns they had were not as critical as they had first envisaged, but rather were ways of protecting themselves in case they failed to make the changes they wanted in their classrooms. The difficulties that many teachers face when introduced to new approaches in the classroom is how to work these new ideas into their existing practice so that a different overall practice emerges (Priestly & Sime, 2005 Cochran-Smith, 1994). Teachers are therefore challenged to justify not only to themselves but also to their students, colleagues and other interested parties as to why they are bringing in these new practices.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…In later interviews, many had either gained confidence to pursue their individual developmental goals or recognised that the concerns they had were not as critical as they had first envisaged, but rather were ways of protecting themselves in case they failed to make the changes they wanted in their classrooms. The difficulties that many teachers face when introduced to new approaches in the classroom is how to work these new ideas into their existing practice so that a different overall practice emerges (Priestly & Sime, 2005 Cochran-Smith, 1994). Teachers are therefore challenged to justify not only to themselves but also to their students, colleagues and other interested parties as to why they are bringing in these new practices.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Research literature on teachers' collaboration and reflective practices has shown that professional exchange about teaching can boost professional development where as its absence can have a negative effect (Arthur et al 2010;Beresford and West 1998;Brady 2009;Bryk et al 1999;Butler et al 2004;Conner 2004;Day, Hadfield and Kellow 2002;Huntley 2005;Hopkins and Stern 1996;Hopkins, Naysmith and Palma 1998;Jolliffe and Hutchinson 2007;Lieberman 2009;McCotter 2001;Minnet 2003;Priestley and Sime 2005;Sarsar 2008;Saunders 2005;Talbert and McLaughlin 2002;Wilson 2008). With this study, I explored further why reflection on practice which remains private can have a limiting effect on professional development.…”
mentioning
confidence: 87%
“…Whilst there are pockets of successful implementation reported in schools: in England (e.g., ; in Scotland (e.g., Priestley & Sime, 2005); in Conceptualizing pre-emptive formative assessment 173…”
Section: Experiences In the Implementation Of Formative Assessmentmentioning
confidence: 98%